NFPE: report to donors on phase I , January 1993-March 1996 - BRAC (© BRAC, 2016)
1. Introduction 2. Programme purpose and objectives 3. FInancial support and expenditure 4. Overall implementation 5. An overview of NFPE 6. Gender issues 7. NFPE management 8. Quality and curriculum 9. Training and development 10. Continuing education 11. NFPE-RDP synergy 12. ESP 13. Monitoring 14. Research and valuation 15. Beyond Bangladesh 16. NFPE evaluation and BRAC'S response.